Sex Differences in Use of Low Tidal Volume Ventilation in COVID-19—Insights From the PRoVENT–COVID Study - Swart, Pien; Nijbroek, Sunny G. L. H.; Paulus, Frederique; Neto, Ary Serpa; Schultz, Marcus J. (Frontiers in Medicine, 2022)
Background. The purpose of this study was to compare and understand differences in use of low tidal volume ventilation (LTVV) between females and males with ARDS related to coronavirus disease 2019 (COVID–19). Methods. Posthoc analysis of an observational study in invasively ventilated patients with acute respiratory distress syndrome (ARDS) related to COVID–19 in 22 ICUs in the Netherlands. The primary endpoint was use of LTVV, defined as having received a median tidal volume (VT) ≤ 6 ml/kg predicted body weight (PBW) during controlled ventilation. A mediation analysis was used to investigate the impact of anthropometric factors, next to the impact of sex per se. Results. The analysis included 934 patients, 251 females and 683 males. All patients had ARDS, and there were no differences in ARDS severity between the sexes. At the first day of ventilation, females received ventilation with a higher median VT compared to males (6.8 [IQR 6.0–7.6] vs 6.3 [IQR 5.8–6.9] ml/kg PBW; P<.001). Consequently, females received LTVV less often than males (23 vs 34%; P=.003). The difference in use of LTVV became smaller, but persisted over the next days (27 vs 36%; P=.046 at day 2, and 28 vs 38%; P=.030 at day 3). The difference in use LTVV use was significantly mediated by sex per se (average direct effect of female sex, 7.5% [95%–confidence interval, 1.7 to 13.3%]; P=.011), and by differences in body height (average causal mediation effect, –17.5% [–21.5 to –13.5%]; P<.001), but not by differences in actual body weight (average causal mediation effect, 0.2% [–0.8 to 1.2%]; P=.715). Conclusions. In this cohort of patients with ARDS related to COVID–19, females received LTVV less often than males in the first days of invasive ventilation. The difference in use of LTVV was mainly driven by an anthropometric factor, namely body height. Use of LTVV may improve by paying attention to correct titration of VT, which should be based on predicted body weight, which is a function of body height.